Optimizing Rejected Oranges into Multipurpose Products in Seribu Jandi Village - Sofyan, Rudy; Ginting, Nurzainah; Masythah, Zuhrina; Ginting, Junita Setiana (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
One of the programs in the 8th Sustainable Development Goals (SDGs) is "Supporting inclusive and sustainable economic growth, full and productive employment, and decent work for all", with the target of achieving higher levels of economic productivity through certification, technological quality improvement, and innovation. Seribu Jandi Village, located in Simalungun Regency, is a center for orange producers. However, some of the oranges produced are categorized as rejected oranges. The main problems faced by orange farming communities in this village are the high volume of rejected oranges and their lack of understanding of processing rejected oranges. As a result, the rejected oranges are only thrown away which pollute the environment. Therefore, it is necessary to take corrective actions by processing rejected oranges into multipurpose products, such as biocatalysts, biodisinfectants, and floor cleaning fluids. Biocatalysts can be used to optimize the absorption of soil elements by orange plants, which certainly will maximize the use of fertilizers. Biodisinfectants are more recommended to be used than chemical disinfectants because chemical disinfectants have side effects that can cause irritation to human skin. Cleaning liquid can be used instead of chemical cleaning fluid, which also has an impact on the environment. In relation to this problem, it is necessary to carry out a series of activities that will greatly help the orange farming community in Seribu Jandi Village. The activities to be carried out are conducting training and counseling on the utilization of rejected oranges into multipurpose products.